ID 292 – Attention modulation during motor preparation in elderly subjects, freezers and non-freezers patients with Parkinson's disease: A time-frequency EEG study. Issue 3 (March 2016) - Tard, C.; Dujardin, K.; Bourriez, J.; Molaee-Ardekani, B.; Derambure, P.; Defebvre, L.; Delval, A.
Abstract : Objective: Freezing of gait in Parkinson's disease seems to result from different factors including attention disorders. Our objective was to explore cortical integration of attentional stimulus during motor preparation. Methods: Three groups were recruited: older people ( n = 6) and parkinsonian patients with ( n = 7) or without ( n = 7) freezing of gait. Attention was modulated during postural preparation of the step by an auditory oddball discrimination task consisting in discriminating a target sound among a series of standard ones. The primary endpoint was quantification of EEG oscillations following the attentional stimulus. Results: An increase of power in low frequencies (delta and theta bands) occurred during the 500 msec following the target stimulus, followed by a decrease in mild frequencies (alpha and beta bands). For freezers patients, early event-related synchronization after the attention stimulus was preserved, whereas EEG oscillations in alpha and beta band were impaired, with a specific impairment to generate an event-related desynchronization after the perception of an attentional stimulus. Conclusions: Early attentional discrimination was efficient in freezers patients. At the opposite, further mechanisms reflecting post-discrimination processing were deficient in those patients. Key message: Cortical modulations during the attention – motor preparation coupling are different in parkinsonian patients with freezing of gait.